SIGNIFIKANSI PERAN PEMERINTAH DALAM PEMYELENGGARAAN JAMINAN PRODUK HALAL DI ACEH - Junia Farma; Fithri Mawaddah (Al-Iqtishadiyah: Ekonomi Syariah dan Hukum Ekonomi Syariah, 2022)
This study aims to examine the signification of the role of the Banda Aceh City government in ensuring the availability of halal food. This research uses a descriptive method of analysis, and the data obtained are analyzed qualitatively. The results showed that the reasons for the importance of the government's role in creating regulations to ensure the availability of halal food are, first; the normative principle of ta'abbudi every Muslim is obliged to consume halal food, second, the modern production system as a result of advances in food technology, third, the inability of consumers to evaluate food even when it has been consumed. For this purpose, the Banda Aceh City Government as the element most related to the community plays a role through the regulations of Mayor Regulation No. 13 Tahun 2011 and No. 16 Tahun 2016. With this goal, the Government of Aceh has established a rule of law that can protect the public from products that are not halal, namely through Qanun Aceh No. 8 Tahun 2016. However, these rules still require regulations / rules to supervise and enforce as a control function so that the form of information regulation, control of producer behavior and preliminary permits synergize in ensuring the availability of halal food. Penelitian ini bertujuan untuk mengkaji signifikasi peran pemerintah Kota Banda Aceh dalam menjamin ketersediaan makanan halal. Penelitian ini menggunakan metode deskriptif analisis, dengan jenis penelitian kualitatif. Hasil penelitian menunjukkan alasan pentingnya peran pemerintah dalam merumuskan regulasi guna menjamin ketersediaan makanan halal yakni, pertama; prinsip normatif ta’abbudi setiap muslim wajib mengkonsumsi makanan halal; kedua, sistem produksi modern sebagai akibat kemajuan teknologi pangan ketiga, ketidakmampuan konsumen mengevaluasi makanan bahkan ketika telah dikonsumsi. Untuk kepentingan tersebut, Pemerintah Kota Banda Aceh sebagai unsur yang paling berhubungan dengan masyarakat telah berperan melalui regulasi Peraturan Walikota No. 13 Tahun 2011 dan No. 16 Tahun 2016. Dengan tujuan tersebut pula, Pemerintah Aceh membuat aturan hukum untuk melindungi masyarakat dari produk non-halal, yakni melalui Qanun Aceh Nomor 8 Tahun 2016. Namun aturan tersebut masih memerlukan regulasi/aturan melakukan pengawasan dan penindakan sebagai fungsi kontrol agar bentuk regulasi informasi, kontrol perilaku produsen dan izin pendahuluan bersinergi dalam menjamin ketersediaan makanan halal.